What you don't know... can't hurt you? A field experiment on relative performance feedback in higher education - Ghazala Azmat; Manuel F. Bagues; Antonio Cabrales; Nagore Iriberri (Queen Mary University of London, School of Economics and Finance, 2016)
This paper studies the effect of providing feedback to college students on their position in the grade distribution by using a randomized control experiment. This information was updated every six months during a three-year period. In the absence of treatment, students' underestimate their position in the grade distribution. The treatment significantly improves the students' self-assessment. We find that treated students experience a significant decrease in their educational performance, as measured by their accumulated GPA and number of exams passed, and a significant improvement in their self-reported satisfaction, as measured by survey responses obtained after information is provided but before students take their exams. Those effects, however, are short lived, as students catch up in subsequent periods. Moreover, the negative effect on performance is driven by those students who underestimate their position in the absence of feedback. Those students who overestimate initially their position, if anything, respond positively.
Keywords: J71; J44; 330; Relative performance feedback; Ranking; Randomized field experiment; School performance